Problems of building defects after handing over the key - Nur Darwani, Abd Rahman (2012)
Building defects can be considered as a normal issue arises in the construction industry in Malaysia. Small defects could lead to serious defects. These building defects can lead to accidents, injury, and time to complete a project longer and costs will be higher. The main purpose of this study was to identify the types of common defects in buildings and main causes for each of the types of defects in the building, to understand the concepts of Defects Liability Period, and to study and identify the rational method for rectifying the building defects. In relation to the objectives, the scope of this study will focus on housing that has been occupied for less than ten (10) years where the buildings are reinforced concrete. Questionnaire session conducted with contractors and owners which are housing residents and were focused around Pahang and Kelantan. Data were analyzed using Average Index Percentage through Microsoft Excel. The study found that seven (7) defect that usually occurs in the building which are wall cracking, plumbing defects, cracked tiles, erosion of mortar joint, roof defects, dampness and unstable foundations. Building defects are caused by shrinkage, water pressure, poor quality materials, movement building, fungal decay, rain water and landslides. The main concept of Defect Liability Period is purposed to rectify the defects in certain period which have been agreed by the contractor and owner. Contractor has their own responsibility and the owner has their own right when the defect occurs. Rational methods were identified to rectify the defects, such as through compressible filler, install the equipment properly, replace with new tile, using suitable mortar, remove and replace the damaged roof with new one, using water repellent treatment and underpinning. Types of defects in the building and the causes should be identified first so that the defects can be rectified with proper and effective methods. The responsible party should give more attention to this problem as serious defects can be avoided.